Seismic vulnerability assessment methodology for historic masonry buildings in the near-field areas. (September 2020) - Mosoarca, Marius; Onescu, Iasmina; Onescu, Eugen; Anastasiadis, Anthimos
Highlights: More than 100 historical masonry buildings are evaluated. Particular failure mechanism in the epicenter is presented. New vulnerability assessment methodology is proposed for the near-field earthquakes. Proposed damage estimation formula calibrated after real damage. Seismic damage scenario presented for macroseismic intensity IX EMS-98. Abstract: Timisoara is the biggest city located in the Banat seismic area, the second most important seismic zone of Romania. The specificity of the area is represented by shallow earthquakes of crustal type, with small focal depths and a PGA = 0.20 g. Because Timisoara was declared the European Capital of Culture 2021, it is mandatory to assess the seismic vulnerability of its most sensitive areas and to design potential losses scenario. This study also provides useful data for the local authorities, helping them develop/improve the prevention and intervention plans. The paper focusses on the analysis of two historical urban districts, likely to be among the most attractive tourist areas. The study aims to assess the seismic vulnerability of the districts in a quick and simplified way, seeks to identify the exposure of the city, and also to provide losses statistics for a specific seismic scenario. The empirical seismic vulnerability assessment methodology is based on European studies and is applied for more than 100 historic buildings. Our assessment analysis aims to adapt the existing seismic assessment methodologies to the near-field earthquake's effects. That is why a new formula is proposed to correlate the empirical vulnerability curves with the actual damage level. The real damage state was observed on similar historical masonry buildings during the site inspection and after the past earthquakes in nearby areas. Besides, a new failure mechanism is highlighted based on the investigation of the effects of previous near-field earthquakes in the Banat seismic region. The new methodology proposes original vulnerability curves, particularly for the near-field earthquakes specific to Banat seismic area.